Causal Factors of Violent Behavior in Patients with Schizophrenia: Literatur Review - Sutini, Titin; Emaliyawati, Etika; Hidayati, Nur Oktavia; Widiasih, Restuning; Ermiati, Ermiati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia causes distortion of thoughts, perception distortions, emotions, and behavior so that patients with schizophrenia have a higher risk of aggressive behavior where dramatic changes in behavior occur within a few days or weeks so that violent behavior is often associated with schizophrenic patients. Violent behavior is a situation where a person performs an action that can harm physically, both to himself and others. Although violent behavior is often associated with schizophrenic patients, not many studies have shown what factors can trigger violent behavior in schizophrenic patients. Aim this study was conducted to determine the factors causing the emergence of violent behavior in patients with schizophrenia. Method. This study uses Qualitative descriptive research approach to find out the description and problems in detail. The source of article data is done using databases and search engines, namely EBSCO, Springer, and Garuda. The strategy used to search the literature is to use the keywords Schizophrenia, Violent Behavior, and Factors. Inclusion criteria in this study were free full text and the year of article published in the range 2012-2022, in Indonesian and English, settings for various geographic locations and settings using the keyword cognitive behavior therapy. Results. Found 383 articles that have a theme according to the keywords entered. Furthermore, full-text article filtering and duplication filtering were carried out to obtain 219 articles. By using the inclusion and exclusion criteria, 6 research articles were obtained which were then analyzed in this study. Article analysis using PRISMA and PICO as the approach.Conclusion. Two main factors cause violent behavior in schizophrenic patients. These factors are predisposing factors such as the patient's personality and history of violence, as well as precipitating factors such as genetics, loss of self-concept, and disharmony in the patient's living environment.